Non-tillage as an agronomical method in basic grain sustainable production. - Rojas, Luis A. (Agronomía Mesoamericana, 2006)
In the present the agriculture and livestock field and specifically the basic grains producer, goes throught the worst crisis in the whole history of Costa Rica. The strong degradation of the natural resourses, linked to the important low yield of the crops, which also coincide with the high cost of production, have been increasing the problem. On the other hand, the lack of policies of the last Costa Rica government hastens the crisis. Right now, the basic grain crops do not produce economic profit, so it’s impossible to contonue producing with high costs, as machinery, excessive use of chemical and other inputs. We are looking for a system to approach and to assess lower cost alternative with high agricultural return. The basic grain sowing within of non-tillage system, conservation tillage o direct sowing, is a great production alternative, with high income and profit in the short, medium and long term; which includes physical, chemical and biological improvement of the soil and reduce the production cost. The Agronomy School at the Costa Rican Tecnological Institute are currently working in the project with different non- tillage activities like research, technological transfer, and non-tillage cropping system in basic grain, as sustainable alternative in the Huetar Norte region of Costa Rica and others parts of the country.